Diabetic Nephropathy, Pathophysiology, Stages and Diagnosis: A Review Study - Aljazaeri, Sarah Ali; AlMmuhammady, Marwa H.; Al-Naji, Noor Hani (Medical Science Journal for Advance Research, 2024)
Diabetic nephropathy was defined as raised protein elimination in urine. The initial stage is characterized by a limited elevation in urinary albumin elimination, also named incipient DN or microalbuminuria. Higher progressive diseases are characterized by the incidence of proteinuria or macroalbuminuria. The recent is typically called overt DN. Diabetic nephropathy, also called diabetic kidney disease, is one of the most prevalent microvascular diseases of the kidneys that results from type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus. Therefore, early disease detection is critical, as DN is the leading cause of renal disease in its latter stages and is associated with an increased risk of death in general, primarily due to cardiovascular disease.